2009
DOI: 10.1080/00288330.2009.9626534
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the distributions of freshwater fishes and decapod crustaceans in urban and forested streams in Auckland, New Zealand

Abstract: Using data from existing studies, assem blages of freshwater fishes and decapod crustaceans were examined at 39 sites in urbanised catchments and 57 sites in forested (reference) catchments within the greater Auckland region, New Zealand. Eleven native and 1 exotic fish species and 2 native decapod crustacean species were recorded. Species richness and fish index of biotic integrity (ibi) scores were lower overall in streams in urbanised catchments. Shortfin eel (Anguilla australis) and mosquitofish (Gambusia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The inhabitants of the p a regarded the Waimapihi Stream as a sacred waterway; it was an important mahinga kai site and a source of water for drinking and irrigation of k umara and flax cultivations (Waitangi Tribunal, 2003). From observations of native fish present in similar streams, the Waimapihi could plausibly have had greater abundance than the contemporary state of aquatic fauna, including inanga and toitoi in addition to the banded k okopu, k oaro and k oura that currently inhabit the Waimapihi (McEwan & Joy, 2009).…”
Section: Containment: the Waimapihi Stream 'Protected' In The Waimapi...mentioning
confidence: 99%
“…The inhabitants of the p a regarded the Waimapihi Stream as a sacred waterway; it was an important mahinga kai site and a source of water for drinking and irrigation of k umara and flax cultivations (Waitangi Tribunal, 2003). From observations of native fish present in similar streams, the Waimapihi could plausibly have had greater abundance than the contemporary state of aquatic fauna, including inanga and toitoi in addition to the banded k okopu, k oaro and k oura that currently inhabit the Waimapihi (McEwan & Joy, 2009).…”
Section: Containment: the Waimapihi Stream 'Protected' In The Waimapi...mentioning
confidence: 99%
“…To obtain the upstream land cover classes surrounding each river, a 1 km buffer was placed around them. To assign each river study site an urban category, a standardised rule was formulated, following McEwan and Joy (2009). The rule classified sites with less than 10%, between 10% and 60%, and greater than 60% upstream urban land covers to be rural, peri-urban and urban, respectively.…”
Section: Characterising the Urban Gradientmentioning
confidence: 99%
“…Providing a diverse range of habitats to support multiple species is important to improve the ecology of the stream, and can include introducing boulders, woody debris, and riparian planting (Neale and Moffett, 2016). During spotlighting in the headwaters, we saw two species of freshwater fish and one decapod, seeing this few species is indicative of what McEwan and Joy (2009) found, that species richness is lower in urbanised streams than forested streams in Aotearoa-New Zealand. However, stream biodiversity is not just about fish, it is the complex interactions between multiple species in stream ecosystems (Paul and Meyer, 2001).…”
Section: Daylighting the Waimapihi Streammentioning
confidence: 73%
“…Contaminants in stormwater that enters the pipes, such as heavy metals and hydrocarbons, have health impacts for the fish, reducing their ability to pass safely through the pipe to the headwaters (McEwan and Joy, 2009). Phill demonstrated the importance of considering the water within the pipe when he suggested that it should be considered as the habitat of the fish.…”
Section: Fish Movement In the Pipementioning
confidence: 99%
See 1 more Smart Citation